2018
DOI: 10.1038/s41426-018-0117-y
|View full text |Cite
|
Sign up to set email alerts
|

Changes in intestinal microbiota in HIV-1-infected subjects following cART initiation: influence of CD4+ T cell count

Abstract: The roles of immunodeficiency and combined antiretroviral therapy (cART) in shaping the gut microbiota in HIV-1-infected subjects (HISs) have not been described thoroughly by time-series investigations. In this study, 36 antiretroviral-naïve HISs were enrolled to prospectively assess alterations in the fecal microbiota and plasma markers of microbial translocation and inflammation with cART. At baseline, the species α-diversity of the fecal microbiota was significantly lower in HISs with a CD4+ T cell count <3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
54
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 38 publications
6
54
0
Order By: Relevance
“…MDC has emerged as novel modulator of lung inflammation in mice 48 and an inflammatory marker to assess the severity of atopic dermatitis in children and infants 49 . More recently, the increased levels of MDC in HIV-infected adults have also been reported 50 . This suggests the potential inflammatory role of MDC in HIV-infected children, however the level of MDC normalizes after initiation of ART.…”
Section: Discussionmentioning
confidence: 87%
“…MDC has emerged as novel modulator of lung inflammation in mice 48 and an inflammatory marker to assess the severity of atopic dermatitis in children and infants 49 . More recently, the increased levels of MDC in HIV-infected adults have also been reported 50 . This suggests the potential inflammatory role of MDC in HIV-infected children, however the level of MDC normalizes after initiation of ART.…”
Section: Discussionmentioning
confidence: 87%
“…It is important to mention that the effect of cART introduction in the modulation of gut microbiota is not completely understood. However, very recently Ji et al showed that this modulation after cART was differentially correlated with the immune status, especially in patients with CD4 + T cell counts>300/mm 3 ( 92 ). In these patients it was shown that the alpha diversity was correlated with CD4 + T cell counts, but the specific role of cART in increasing microbial diversity is still controversial ( 78 , 92 , 93 ).…”
Section: Sources Of Immune Activation and Insulin Resistance In Hiv Pmentioning
confidence: 99%
“…However, very recently Ji et al showed that this modulation after cART was differentially correlated with the immune status, especially in patients with CD4 + T cell counts>300/mm 3 ( 92 ). In these patients it was shown that the alpha diversity was correlated with CD4 + T cell counts, but the specific role of cART in increasing microbial diversity is still controversial ( 78 , 92 , 93 ). This correlation may explain the conflicting results in previous studies investigating alpha diversity in intestinal microbiota in HIV patients ( 93 96 ), indicating that this diversity is consequence of the immune status of the subjects.…”
Section: Sources Of Immune Activation and Insulin Resistance In Hiv Pmentioning
confidence: 99%
“…However, these studies did not consider the immune response to ART and implement few in China [7]. Recently, several studies reported that gut microbiota was associated with CD4 recovery in HIV-infected patients [8][9][10]. The microbiome of chronic HIV infected individuals were studied in China, however, these patients had heterogeneous HIV progression and immune response to ART [11,12].…”
Section: Introductionmentioning
confidence: 99%